ABC - Acid and Base Chemistry: An Android Mobile Learning Media to Improve Students’ Learning Outcomes and Motivation - Kaukaba, Syam Qeisha; Lutfi, Achmad (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2022)
This research aimed to obtain "ABC - Acid & Base Chemistry" android mobile learning media that is valid, practical, and effective in improving students’ learning outcomes and motivation. The developmental model with the stages: defined, design, and development is used in the current study. The instruments used include validation sheets, students’ response questionnaire, learning motivation questionnaire, and pretest-posttest question. Thirty-five students conducted a limited trial at SMAN 3 Sidoarjo. Data analysis using one group pretest-posttest design. Based on the research results, the validity test scored more than three in the valid category. The practicality test of the media with the analysis of the student response questionnaire got a percentage of 96% with a very practical category. The media effectiveness test is seen from the analysis of the students’ learning outcomes obtaining a classical completeness percentage of 88.5%, and a questionnaire analysis of students' learning motivations obtaining an overall average percentage of 95% with a very effective category. It can be decided that the “ABC – Acid & Base Chemistry” android mobile learning has fulfilled the aspects of validity, practicality, and effectiveness as a learning media to improve student learning outcomes and motivation.